Exploring and resolving the effects of environment on perovskite oxide catalysts for oxygen evolution in water electrolysis - Seow, Justin Zhu Yeow (Nanyang Technological University, 2023)
While integration of renewable energy sources can increase the sustainability of electricity generation process, the intermittence of some of these energy sources has affected the ability of the electrical grid to fulfill the time-dependent demand. Energy storage system will be beneficial in resolving this issue, and since hydrogen has high specific energy and compressibility, it has become an attractive large-scale energy storage medium. The greenest way to produce hydrogen is through water electrolysis, but its lack of energy efficiency, mainly limited by oxygen evolution reaction (OER), has reduced its feasibility for commercialization. In various works improving the efficiency of OER, it has become evident that active-site-rich oxyhydroxides formed from surface reconstruction of perovskite oxides are competitive OER catalysts compared to precious metal catalysts.